FUNCTIONS AND STRUCTURE OF THE UNIVERSITY COMPLEX MECHANISM WHICH SERVES EDUCATIONAL INTERESTS - Spivakovsky, О.В.; Alferova, Л.М.; Alferov, Є.А. (Journal of Information Technologies in Education (ITE), 2012)
The article deals with the functions and structure of the university as a corporate complex mechanism which serves educational interests. Its exploration is needed for a more harmonious and balanced passing reformation process and modernization of education in Ukraine in accordance with European trends. Technical model of university was formed and comparison of the university and company structure was made. Some conclusions about existing problems of education process efficiency and the ways of its solutions were made. There are critical modern views on the education system as a competitive member of the economy market in this article.